2008
DOI: 10.1098/rsta.2008.0247
|View full text |Cite
|
Sign up to set email alerts
|

The origin of Titan's atmosphere: some recent advances

Abstract: It is possible to make a consistent story for the origin of Titan's atmosphere starting with the birth of Titan in the Saturn subnebula. If we use comet nuclei as a model, Titan's nitrogen and methane could have easily been delivered by the ice that makes up approximately 50 per cent of its mass. If Titan's atmospheric hydrogen is derived from that ice, it is possible that Titan and comet nuclei are in fact made of the same protosolar ice. The noble gas abundances are consistent with relative abundances found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The instrument simply did not have the sensitivity to detect Kr and Xe given the observed abundance of 36 Ar in any of these reservoirs. Although the processes proposed for the nondetection of krypton and xenon may be operating on Titan, the available data do not reveal or require them [ Owen and Niemann , 2009]. Of course, Titan might have collected its noble gases from a completely different mixture from those we know.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument simply did not have the sensitivity to detect Kr and Xe given the observed abundance of 36 Ar in any of these reservoirs. Although the processes proposed for the nondetection of krypton and xenon may be operating on Titan, the available data do not reveal or require them [ Owen and Niemann , 2009]. Of course, Titan might have collected its noble gases from a completely different mixture from those we know.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of radiogenic 40 Ar, outgassed from Titan's rocky interior, indicates that the interior and atmosphere are connected [ Niemann et al , ]. The nondetection of Kr and Xe is not particularly surprising; the upper limits are consistent with solar abundances and a number of other atmospheres in the solar system [ Owen and Niemann , ]. Additionally, there are a number of possible noble gas sequestration mechanisms, both prior to and after formation: H3+ complexes [ Pauzat et al , ], trapping in hazes [ Jacovi and Bar‐Nun , ], dissolution in lakes and seas [ Cordier et al , ; Hodyss et al , ], and trapping in clathrate hydrates [ Mousis et al , ; Tobie et al , ].…”
Section: The Age and Origin Of Titan's Atmospherementioning
confidence: 99%
“…One possibility is that the icy planetesimals formed at temperatures >75 K so that the noble gases and CH 4 were not captured, but NH 3 and CO 2 were. However, Owen and Niemann (2009) showed that the detection of Ar but not Kr or Xe could instead be due to the limited sensitivity of the Huygens probe instrument given the relative abundance of these elements in other solar system bodies, making such arguments inconclusive.…”
Section: Saturn Systemmentioning
confidence: 94%